PENERAPAN METODE USABILITY PADA SISTEM INFORMASI PELAYANAN PELANGGAN - Tri Rizqi Ariantoro (IIB Darmajaya, 2017)
Usability comes from a usable word that generally means it can be used properly. Basic usability usability levels include: Learnability, efficiency, memorability, error and satisfaction. PDAM Tirta Musi Palembang has a website that is www.tirtamusi.com, and has not been evaluated how far the website is useful (usable), in presenting information and service satisfaction to customers. The usability method can be used to evaluate the website. In the process of website evaluation, usability testing can use the supporting application that is Techsmith Morae Recorder. Morae provides functions to assist usability practitioners in planning, testing, data analysis and reporting of results. From the results of research can be seen that the website PDAM Tirta Musi Palembang not yet meet from the level of satisfaction (satisfaction). Where necessary the addition of information menu is Telephone Information and Company's Complete Address, Service Unit Information, Site Map and Searching. Research using this usability is expected to provide an assessment for the development of the website so that it can be useful and provide satisfaction to customers.Keywords: Usability, Website, Evaluation, and Morae Recorder.